Regalo at sorpresa marketing plan - Bagayana, Jena Dalagan; Cruz, Edison (Quezon City University of the Philippines Diliman, 2015)
With the growing e-commerce industry and technological advances, this paper presents the marketing plan of Regalo at Sorpresa which aims to create value in taking advantage of the online platform, addressing existing dilemma in buying gifts and helping people to maintain good relationships through sending gifts. Regalo at Sorpresa is an online retail store developed to deliver personalized items and requests based on the interest, hobbies, personality, occupation and culture of the target client. In having an in-depth study with this concept, this may enlighten start-up entrepreneurs regarding online retailing in the Philippine scenario.

Factors that may affect the success of Regalo at Sorpresa and the ways how the value of the concept can be gained were determined by conducting a market research involving the actual target market of the business. Insights from potential stakeholders were also gathered through a small focus group discussion. Presented also in this paper were the analysis on the environmental aspect, SWOT and competitive forces to compare the similarities and differences, advantages and disadvantages of Regalo at Sorpresa to those existing businesses with the same platform.

Based on the initial data collected, the marketing objectives, target market and the marketing mix have been conceptualized. The marketing objectives focused on customer satisfaction, market expansion and profitability. The target markets were overseas Filipino workers and FIlipino emigrants who have family, relatives, friends, and dependents living in the Philippines. The marketing mix details were : products and services offered, pricing, position in the market place, promotion, people in the business, process representing the buying experience and physical environment where the goods/services are presented.

The marketing research result shows that a number of respondents were likely to give gifts to their loved ones via Regalo at Sorpresa given with these considerations : affordability and promos, good quality products and fast delivery. The competition involved the existence of physical stores and online shops with proven credibility. Summary of the focus group discussion attended by potential stakeholders includes the creation of a simple and user friendly website, business registration and profitability of the business.

On the financial side of the business, key assumptions as well as revenue and cost projections were computed to make it profitable. The marketing implementation activities focused on the product, marketing strategies, advertising, public relations, market research and promotional activities.

With thorough analysis on the available facts and data, it can be concluded that there is a potential market for Regalo at Sorpresa. The market trends show that increasing number of people are now inclined in buying online. However, critical issues such as fear and doubt of the clients regarding perceived risks should be addressed.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Business planning